ANALISIS PERUBAHAN SIFAT DIFUSI RUANG TERHADAP PENAMBAHAN JALINAN SERAT IJUK - , FAJLI MUSTAFA, Sentagi Sesotya Utami, S.T., M.Sc., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
degree of diffuseness of The the space can be measured using the coherence of two or more measurement positions. The value of coherence can be determined using manual calculation, Matlab calculation and software Realtime Analyzer. An experiment has done in a semi-anechoic chamber. From the determinations of coherence show that Matlab calculation is the most appropriate method to determine the coherence value. It can be shown from the value of coherence in the empty room and changes with addition woven sugar palm husk and woven coconut husk. With Matlab calculation, addition the woven sugar palm husk 1 layer increased the value of coherence better than addition woven sugar palm husk 2 layers at frequency 125 Hz, 500 Hz, 2000 Hz, 4000 Hz and 8000 Hz. It shows that adding the woven sugar palm husk 1 layer makes the degree of diffuseness of the space better than using 2 layers. This is because the woven sugar palm husk 2 layers has absorption degree higher than 1 layer. And with addition the woven sugar palm husk notched layer increased the value of coherence better than adding the woven sugar palm husk 2 layers at frequency 500 Hz, 1000 Hz, 2000 Hz, 4000 Hz and 8000 Hz. It shows that addition the woven sugar palm husk notched layer makes the degree of diffuseness of the space better than using 2 layers. This is because the woven sugar palm husk notched layer has surface shape that can spread the reflection better than 2 layers. However, the amount of absorption by the materials affect more significantly than the surface shape